Canine spinal cord neuron and axon myelin sheath morphometry - Carvalho, A. C. de Francischini; Pacheco, M. R.; Artoni, S. M. Baraldi; Mateus, O. (Blackwell Publishing, 2006)
This inedited morphometric study has been developed from healthy canine spinal cord neuron cytoplasm and nucleus, and white matter axonal myelin sheath, from cervical, thoracic and lumbar regions. For the morphometric study, the parameters were area, perimeter, maximum and minimum diameters and roundness for neurons and myelin thickness for axon. For each parameter, 300 neurons were analysed. The results revealed that lumbar neurons had the highest mean values for the analysed parameters, indicating the presence of large neurons in this region, with large axons as a result of myelin thickness, which is proportional to axon calibre. We conclude that these morphometric results can contribute for the establishment of normal patterns, for canine spinal cord cervical, thoracic and lumbar segments.